Bibliografie w badaniach historyczno-pedagogicznych. Refleksje na marginesie książki Renaty Bednarz-Grzybek, Moniki Hajkowskiej pt. Edukacja zdrowotna i turystyka uzdrowiskowa z perspektywy polskojęzycznej prasy uzdrowiskowej (1844–1914). Bibliografi - Kabacińska-Łuczak, Katarzyna (Biuletyn Historii Wychowania, 2026)
This paper is inspired by the monograph by Renata Bednarz-Grzybek and Monika Hajkowska, Health Education and Spa Tourism from the Perspective of Polish-Language Spa Press (1844-1914) . Bibliography, Lublin 2024. Its aim is to reflect on the significance of bibliographies (particularly specialized ones) in historical and teaching research.